Liberty!': Freedom Rings; A Gripping Account of the Birth of a Nation: FINAL Edition - Grove, Lloyd (The Washington post, 1997)
For people who think of the Founding Fathers as a bunch of dead white guys chiseled in marble -- and of the war they fomented as the stuff of a dogeared schoolbook -- public television's "Liberty! The American Revolution" should come as a revelation. Stirring, moving and occasionally surprising, this six-part series on PBS -- airing two parts at a time tomorrow, Monday and Tuesday nights at 9 -- takes a venerable subject, the birth of American democracy, and reveals it afresh. Over the course of six hours, viewers will learn that: George Washington was a pretentious dandy who complained churlishly to his London tailor about the prices of clothes; John Adams was a socially insecure country lawyer who craved public attention but considered himself "unpopular and obnoxious"; and Benjamin Franklin was an oily operator who mixed business and politics in ways that might even shock Bob Strauss. These men were also idealists and visionaries -- and "Liberty!" shows compellingly just why and how they were.